The Implementation of Independent Learning Curriculum in Social Sciences Studies at SMP Unggulan 9 Pulau Morotai - Jaguna, Fahmi (International Journal of Education, Information Technology, and Others, 2023)
The aim of this research is how to describe the planning process, implementation process and evaluation process in the implementation of the Independent Learning Curriculum in Social Studies Learning at SMP Unggulan 9 Morotai Island. The approach used in this research is qualitative research or a descriptive qualitative approach. Data collection techniques use observation, interviews and documentation. For data analysis, the researcher carries out several steps, namely data reduction, data display and conclusion drawing. Meanwhile, in testing the validity of the data, researchers used data triangulation techniques. The results are related to the implementation of the Merdeka Belajar Curriculum in Social Studies Learning at Unggulan 9 Middle School on Morotai Island, where social studies learning planning has been implemented quite well, because it is able to create a differentiated learning process. In the implementation of social studies learning, it has also been carried out quite well. It is able to carry out learning implementation based on the implementation of the independent learning curriculum. Meanwhile, the evaluation aspect of social studies learning in the Independent Learning Curriculum at Superior Middle School 9 Morotai Island was carried out well. Social studies teachers also use assessments according to the objectives of the independent learning curriculum, namely starting from formative assessments, projectbased assessments and also using assessment instruments for students.